Herbal remedies for oligomenorrhea in Traditional Persian Medicine - Arezoo Moini Jazani; mojgan Tansaz; Ramin Nasimi Doost Azgomi; Mohammad Bagher Fazljoo; Kobra Hamdi (Shiraz University of Medical Sciences, 2016)
Sir,We've read with much eagerness the article entitled "An overview of amenorrhea and respective remedies in Traditional Persian Medicine," published in your venerable journal. The honorable authors compiled herbal remedies of amenorrhea in Traditional Persian  Medicine(TPM). Based on the findings of this study, 71 medicinal plants were found as emmenagogue in medical and pharmaceutical manuscripts of Persian medicine.The authors have also mentioned that only Foeniculum vulgare had therapeutic effects on amenorrhea in a randomized placebo-controlled trial.In a comprehensive survey, we searched the principle medical and pharmaceutical text books of Persian Medicine to extract and amass medicinal materia causing menstruation and then we also searched databases to achieve any evidance for the efficiency of the plants on amenorrhea. So we want to remind some points about the article issue and their findings.Selection proper key word is indispensable and helpful to search more completely  and exhaustively. According to the article issue, Using "Moder" as a main keyword may be necessary but the respectable authors have not exerted this essential key word. Based on the findings of our study, more than 150 medicinal plants have been mentioned as emmenagogue in ancient Persian Medicine  text books. Some of these herbal remedies are Vitex agnus-castus, Sesamum indicum, Paeonia lactiflora, Artemesia vulgaris L, Bitter Almond, Peganum harmala,  Ricinus communis, Valeriana officinalis, Brassica oleracea, Marrubium vulgare L,... that were not mentioned in the article. The difference in the keywords and failure to use the term "Moder" and its synonym in Arabic as a main keyword make differences in the findings(1-4).The strategy of search in data bases is not very clear.The worshipful authors did not mention that by what keywords emmenagogue activities of  plants have been searched in data bases. In addition to amenorrhea, oligomenorrhea, menstruation and ..., we searched by some other keywords like PCOs or hyperandrogenism which are the causes of amenorrhea. So despite of few studies in this field, addition to clinical study on fennel, emmenagogue effect of another more plants like Mentha longifoli, Vitex agnus-castus, Sesamum indicum, Cinnamomum verum, Trigonella foenum-graceum L.and Urtica dioica have been reported in some clinical trials(5-10).Plants with different mechanisms may be effective on menstruation. Some possible mechanisms like lowering LH and prolactin in addition to estrogenic activity have been expressed for inducing menstruation in different studies(11, 12).